Karakteristik Torrefaksi dan Densifikasi Limbah Tandan Kosong Kelapa Sawit - Maryudi Maryudi (CHEMICA: Jurnal Teknik Kimia, 2016)
Energy demand increases continuously due to the growth of industries. Most industries still rely on fossil fuel and its price commonly increases and the deposit in the universe decreases since it is not a renewable resource. Indonesia is the largest palm oil producer in the world that has potential abundance biomass of empty fruit bunch (EFB) of oil palm. It can be an alternative energy source. The EFB is commonly used as fuel for the heat source of boiler in the palm oil plant. Most applications were by conventional combustion process that has the disadvantage of low energy value. The EFB was only chopped and grinded, and then dried prior to the combustion process. This study investigates the improvement of energy quality of EFB through torrefaction (or light pyrolysis) and the densification process. The EFB was chopped in small size and grinded in the form of fiber, then dried. The EFB fiber in small slices was pressed in a small steel tube and heated in the range of 200-300 °C. The variables of the study were the duration and temperature of the process. The initial heat value of EFB was 18,241 MJ/kg that slightly lower than its kernel shell heat value of 19,955 MJ/kg. The water content was found at 6.28% and 4.31% for EFB and kernel shell respectively. Results have shown that torrefaction and densification have improved the calorific value of EFB in the range of 6.58-16.71% of its initial value. On the other hand, the energy yield has decreased to 97.54, 97.26, and 93.76% of its initial energy yield for torrefaction temperature of 200, 250, and 300 °C respectively.